Three Major Interrelated Factors Contributing to Homelessness Issue among Former Prisoners in Malaysia - Bin Jasni, Mohd Alif; Abu Bakar Ah, Siti Hajar; Che Mohd Nasir, Norruzeyati (International Journal of Criminology and Sociology, 2022)
Homelessness issue among former prisoners in Malaysia upon their release is of great concern. Hence, this study aimed to identify the predominant factors influencing homelessness issue among former prisoners in Malaysia. Imprisonment is usually assumed to be a negative life event and can act as a hindrance for the former prisoner to successfully integrate after being freed from prison. Imprisonment and past criminal records are the biggest contributors to becoming homeless. This is a fact because imprisonment causes the former prisoners to lose his source of income, personal belongings, ability to seek shelter and personal relationships due to family rejection, addiction and unemployment. This study was based on the Ecological Model of Homeless by Nooe and Patterson. The selection of this model was considered appropriate and aligned with the objectives of the study which aimed to identify the factors that lead to the life of the homeless among former prisoners. In this study, nineteen former prisoners, regardless of the type of offence committed, were selected using the snowball sampling method and were interviewed. The findings revealed that family denial, unemployment, and drug addiction were the three major interrelated factors that contribute to the homelessness issue among the former prisoners during their reintegration process. Housing security is a risk factor of homelessness.